Modeling of Diffuse Auroral Emission at Mars: Contribution of MeV Protons. Issue 1 (19th January 2022) - Nakamura, Yuki; Terada, Naoki; Leblanc, François; Rahmati, Ali; Nakagawa, Hiromu; Sakai, Shotaro; Hiruba, Sayano; Kataoka, Ryuho; Murase, Kiyoka
Abstract: The Solar Energetic Particle and imaging ultraviolet spectrograph (IUVS) instruments onboard the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft discovered diffuse aurora that span across the nightside of Mars due to the interaction of solar energetic particles (SEPs) with the Martian atmosphere. However, it is unclear whether the diffuse aurora originates from energetic electrons or protons. We have developed a Monte Carlo model to calculate the limb intensity profile of the CO2 + ultraviolet doublet (UVD) due to precipitation of energetic electrons and protons with energy ranges from 100 eV to 100 keV and from 50 keV to 5 MeV, respectively. We used electron and proton fluxes observed by MAVEN during the December 2014 SEP event and the September 2017 SEP event. Our results showed that proton‐induced CO2 + UVD emission has a lower peak altitude than electron‐induced CO2 + UVD emission. The calculated peak altitudes of the CO2 + UVD limb profiles are 76 and 68 km in the December 2014 event and the September 2017 event, respectively. Extending the energy to 500 keV for electrons and 20 MeV for protons further improved our comparison to the IUVS observations. We have succeeded in reproducing peak altitudes and shapes of the observed CO2 + UVD limb profiles using the SEP flux observed by MAVEN. This was possible by taking into account the contribution of energetic protons, indicating that both energetic electrons and protons contribute to producing the observed diffuse aurora. Key Points: A Monte Carlo model was developed to investigate the contributions of precipitating electrons and protons to the diffuse auroral emission Proton‐induced CO2 + ultraviolet doublet (UVD) emissions have lower peak altitudes than electron‐induced emissions The Mars Atmosphere and Volatile EvolutioN/imaging ultraviolet spectrograph (IUVS) limb emission profiles of CO2 + UVD during two solar energetic particle (SEP) events were reproduced by considering the contribution of SEP protons